Filtration of Giardia cysts and other substances. Volume 1, Diatomaceous earth filtration - Bellamy, William D., author; Lange, Kelly P., author; Hendricks, David W., author; U.S. Environmental Protection Agency, Municipal Environmental Research Laboratory, publisher (Colorado State University. Libraries, 1984)
The effectiveness of diatomaceous earth filtration of drinking water was studied under various operating conditions for removal of Giardia lamblia cysts, total coliform bacteria, standard plate count bacteria, turbidity, and particles. Hydraulic loading rates imposed were 2.44, 4.88, and 9.76 m/hr (1, 2, and 4 gpm/ ft2) . Seven grades of diatomaceous earth were used. Temperatures ranged from 5° to 19°C, and concentrations of Giardia cysts and bacteria were varied over two or more log cycles. Giardia lamblia is a protozoan prevalent in the clear, cool waters characteristic of the Rocky Mountain region. This organism causes giardiasis, a harmful but nonfatal intestinal disease. Many communities use water from these Rocky Mountain streams, which are considered pristine pure because they look aesthetically pleasing and will meet the 1-NTU turbidity water quality standard. How to treat these waters has become an important concern over the last few years as outbreaks of giardiasis have occurred. Economical and effective filtration systems are needed for the removal of Giardia cysts. Designs appropriate for small water systems are particularly needed. Diatomaceous earth filtration was one system studied for such application. This study shows that diatomaceous earth filtration is an effective process for water treatment. Giardia cyst removals were greater than 99.9 percent for all grades of diatomaceous earth tested, for hydraulic loading rates of 2.44 to 9.76 m/hr, and for all temperatures tested. Percent reductions in total coliform bacteria, standard plate count bacteria, and turbidity are influenced strongly by the grade of diatomaceous earth used. The coarsest grades of diatomaceous earth recommended for water treatment (e.g., C-545) will remove greater than 99 percent of Giardia cysts, 95 percent of cyst-sized particles, 20 to 35 percent of coliform bacteria, 40 to 70 percent of heterotrophic bacteria, and 12 to 16 percent of the turbidity from Horsetooth Reservoir water. The use of the finest grade of diatomaceous earth (i.e., Filter-Cel), or the use of the coarse grades with alum coating, will increase the effectiveness of the process, resulting in 99. 9 percent removals of bacteria and 98-percent removals of turbidity. This report is one of three that will deal with filtration of Giardia cysts and other substances. Volume 2 deals with slow sand filtration and Volume 3 deals with rapid sand filtration. This report covers the period March 1, 1981 to February 28, 1984, and work was completed as of February 28, 1984.
Diatomaceous earth filtration
CER83-84WDB-KPL-DWH37a.
March 1984.
This report was submitted in fulfillment of Contract No. CR808650-02 by Colorado State University under the sponsorship of the U.S. Environmental Protection Agency.
Keywords: Drinking water -- Purification -- United States; Water -- Purification -- Diatomaceous earth filtration; Filters and filtration; Giardia lamblia